Tomás de Aquino y el principio de inteligibilidad (regularidad) de la naturaleza : la cuestión de los universales y la Lex Naturalis en la filosofía de Santo Tomás - Contreras, Sebastián (Sapientia, 2010)
The debate is based on the fact that the ultimate reference of universals is to be found in concrete-contingent reality (on the finite sphere), though provided with a certain order, a certain reflected intelligibility. Universals do not actually exist in reality, only singular beings do, through which abstraction and knowledge are enabled. Therefore, the universal is a “sign” of the nature of things, which makes predication possible. We have proposed an evaluation of the solution that Thomism offers to the problem of universals following the correlation between “essence” and “being”. We have taken as a starting point the two-fold state of the quidditas in Saint Thomas Aquinas’ metaphysics.